Synthesis of substituted trinaphthylenes - Rüdiger, Elias; Rominger, Frank; Steuer, Lena; Bunz, Uwe H. F. (The journal of organic chemistry, 2016)
A short synthesis of six trinaphthylenes is reported. The cyclotrinaphthylenes carry six alkoxy groups, and derivatives featuring OHex, OBu, OiPr, OPr, OEt, and OMe substituents can be obtained by an ordinary Ni(COD)2-promoted, Yamamoto-type coupling reaction. Cyclotrimerization yields range from 38% to 65%. Dependent upon their structure, the cyclotrinaphthylenes assume different packing patterns, according to single-crystal X-ray structure determination. The crystal structures of such trinaphthylenes were hitherto undescribed.